What Is the Real Impact of Schooling on Age of First Union and Age of First Parenting? New Evidence from Guatemala - Behrman, Jere R.; Murphy, Alexis; Quisumbing, Agnes; Ramakrishna, Usha; Young, Kathryn (World Bank, Washington, DC, 2012)
The ages of first union and of first parenting are of considerable interest, not only because of their implications for individual welfare and well-being over the life cycle, but also because they are strongly associated with fertility patterns that are thought to have important implications for the broader society. But the many positive associations between schooling attainment and ages of first union and first parenting do not mean that increasing education causes increases in ages of first union and first parenting. This study contributes to the literature by investigating the impact of schooling on ages of first union and first parenting using data collected over 35 years in Guatemala. It advances beyond the previous literature by (1) treating schooling as behaviorally-determined, which changes the estimated schooling impacts considerably in a number of cases, tending to result in stronger positive effects of schooling for females and weaker ones for males; (2) including other aspects of individuals' human capital and parental family background, which in some cases changes the estimated impact of schooling attainment a fair amount; and (3) including outcomes, additional to ages of first union and first parenting, such as union partner's human capital and union partner's family's social and economic status, which enriches the understanding of the multiple effects that schooling attainment has on the processes under study.